Robust frequency stabilization in a microgrid system - Vachirasricirikul, S.; Ngamroo, I.; Kaitwanidvilai, S.; Chaiyatham, T. (My University, 2009)
This paper proposes a new design of a robust control and monitoring system (RCMS) for robust stabilization of frequency fluctuation in a microgrid (MG) system. In MG system, the power sources consists of wind power (WP), photovoltaic (PV), microturbine (MT) and fuel cell (FC). Due to WP, PV and load fluctuations, the frequency stabilization of RCMS is performed by adjusting the power outputs of MT and electrolyzer system (ES) in both islanding and interconnected utility grid operations. The structure of MT and ES controllers is a proportional integral (PI). To enhance the robustness of designed controllers against system uncertainties, controller parameters of MT and ES are concurrently tuned by the particle swarm optimization based on a specified-structure H∞ loop shaping control. Simulation results display the effectiveness and robustness of the proposed RCMS against system parameters variation and several operating conditions.
Keywords: H∞ loop shaping control; Microgrid; Particle swarm optimization; Robust control